The Zapatistas’ CompArte por la Humanidad: "Art that is neither seen nor heard" - Martínez González, Rocío Noemi (Re-visiones, 2024)
This document seeks to give an account on the significance of the event called CompArte por la humanidad (‘CompArte for Humanity’), as organised by the Ejército Zapatista de Liberación Nacional (the EZLN, i.e. the Zapatista Army of National Liberation) in 2016 (and extended to 2018). The event CompArte entailed, as its name suggests, the sharing of creative practices, inviting “artists” to transform the world by means of doing. Thus, the Zapatistas took it upon themselves to conceive and make artworks that were mostly collective, between the mountain and the jungle, to take part in this international event. One of the main objectives was based on the direct opposition between creation and destruction, to show that a different world and different kinds of social relationships, among the actors of history, are possible. The words of Subcomandante Moisés, on the 3rd August 2016, in the statement titled “El arte que no se ve ni se escucha” (‘Art that is neither seen nor heard’), speak of the art made by the Zapatistas, in the creation of indigenous cultures and in the act of doing from below. Where the ability to create can transform us as people and collectivities and where the act of making art is no longer a commodity, but rather a materiality with body and soul, with a voice that is painted, embroidered, sung and danced, becoming thus the boundary-crossing voice of those “without a voice”, those who are neither seen nor heard.